Computational Methods in Engineering &Amp; Science 2006
DOI: 10.1007/978-3-540-48260-4_50
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear FE Model for RC Shear Walls Based on Multi-Layer Shell Element and Micro-Plane Constitutive Model

Abstract: Nonlinear simulations for structures under disasters have been widely focused on in recent years. However, precise modeling for the nonlinear behavior of reinforced concrete (RC) shear walls, which are the major lateral-force-resistant structural member in high-rise buildings, still has not been successfully solved. In this paper, based on the principles of composite material mechanics, a multi-layer shell element model is proposed to simulate the coupled in-plane/out-plane bending and the coupled in-plane ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 5 publications
0
12
0
3
Order By: Relevance
“…If the amount of the steel reinforcement distributed in longitudinal and transversal directions of the concrete is the same, the layer of steel is introduced as isotropic. But, if the amounts of steel in the two directions are different, a reinforcement layer with two 1664 EC 32,6 orthotropic main axes is used (Miao et al, 2006;Băetu and Ciongradi, 2011). In the model used herein, five layers have been defined, one corresponding to the confined and unconfined concrete in the wall and its boundaries and four corresponding to the reinforcement in the horizontal and vertical directions on both sides of the wall section ( Figure 3) (Sap2000 V14 Help, 2009).…”
Section: Description Of the Layered Shell Element For The Structural mentioning
confidence: 99%
“…If the amount of the steel reinforcement distributed in longitudinal and transversal directions of the concrete is the same, the layer of steel is introduced as isotropic. But, if the amounts of steel in the two directions are different, a reinforcement layer with two 1664 EC 32,6 orthotropic main axes is used (Miao et al, 2006;Băetu and Ciongradi, 2011). In the model used herein, five layers have been defined, one corresponding to the confined and unconfined concrete in the wall and its boundaries and four corresponding to the reinforcement in the horizontal and vertical directions on both sides of the wall section ( Figure 3) (Sap2000 V14 Help, 2009).…”
Section: Description Of the Layered Shell Element For The Structural mentioning
confidence: 99%
“…Nonlinear modeling parameters of beams and columns were selected based on the recommendation of FEMA 356 [9]. The inelastic behavior of concrete shear walls was considered using fiber element method [10]. From the results of NTH analysis it was found that, the first critical location for monitoring the moment values was located at the intersection of axis C and axis 2.…”
Section: Fe Model and Nonlinear Time History Analysismentioning
confidence: 99%
“…This element is able to model essential mechanical elastic and inelastic characteristics of reinforcement as concrete and steel materials separately. The proposed layered shell element is based on the principles of composite material mechanics and it can simulate the coupled in-plane/out-plane bending and the coupled in-plane bending-shear nonlinear behaviours of a RC shaft [20]. The multi-layer shell element is a combination of a number of layers where reinforcement and concrete was assigned separately (Figure 4).…”
Section: Finite Element Modelmentioning
confidence: 99%